Juridical Analysis of Disharmonization between Local Leaders and Deputy Local Leaders in Local Government Systems - Agustina, Enny (Research and Development Agency Ministry of Home Affairs, 2020)
The relationship between the Local Leaders and Deputy Local Leaders often creates conflicts to disharmony. Reduced harmony between the Local Leaders and Deputy Local Leaders occurs in many regions in Indonesia. This study discusses the factors that Cause Disharmony between the Local Leaders and Deputy Local Leaders in the Government System and the Ideal Position of Deputy Local Leaders in the Decentralization System. The data collection method used in this study is library research. Literature research collects relevant data and information by books, magazines, articles, journals, writings, and legislation relating to the issues raised in this study. The research and discussion results in this study are the factors that cause disharmony between the Local Leaders and Deputy Local Leaders in the Local Government System are First, Political Maturity. Second, the unequal distribution of power and race to politicians. While the duties of Deputy Local Leaders regulated in Law No. 23 of 2014 concerning Local Government, where most of the first, assisting Regional Heads in Leading the implementation of local government affairs, Secondly, giving advice and consideration to Local Leaders in carrying out Local Government affairs. Third, carry out the Local Leaders’ daily tasks if the Local Leaders serve a period of detention or temporarily unavailable. Fourth, carry out other duties and authorities by statutory regulations.